Characterization of opioid consumption and disposal patterns after total knee arthroplasty. (July 2019) - Premkumar, A.; Lovecchio, F. C.; Stepan, J. G.; Sculco, P. K.; Jerabek, S. A.; Gonzalez Della Valle, A.; Mayman, D. J.; Pearle, A. D.; Alexiades, M. M.; Albert, T. J.; Cross, M. B.; Haas, S. B.
Abstract : Aims: The aim of this study was to determine the general postoperative opioid consumption and rate of appropriate disposal of excess opioid prescriptions in patients undergoing primary unilateral total knee arthroplasty (TKA). Patients and Methods: In total, 112 patients undergoing surgery with one of eight arthroplasty surgeons at a single specialty hospital were prospectively enrolled. Three patients were excluded for undergoing secondary procedures within six weeks. Daily pain levels and opioid consumption, quantity, and disposal patterns for leftover medications were collected for six weeks following surgery using a text-messaging platform. Results: Overall, 103 of 109 patients (94.5%) completed the daily short message service (SMS) surveys. The mean oral morphine equivalents (OME) consumed during the six weeks post-surgery were 639.6 mg (sd 323.7; 20 to 1616) corresponding to 85.3 tablets of 5 mg oxycodone per patient. A total of 66 patients (64.1%) had stopped taking opioids within six weeks of surgery and had the mean equivalent of 18 oxycodone 5 mg tablets remaining. Only 17 patients (25.7%) appropriately disposed of leftover medications. Conclusion: These prospectively collected data provide a benchmark for general opioid consumption after uncomplicated primary unilateral TKA. Many patients are prescribed more opioids than they require, and leftover medication is infrequently disposed of appropriately, which increases the risk for illicit diversion. Cite this article: Bone Joint J 2019;101-B(7 Supple C):98–103